Sosialisasi dan Pemberian Puding Daun Kelor (Moringa Oleifera) Sebagai Upaya Pencegahan Stunting pada Balita di Posyandu Desa Ngombakan, Kecamatan Polokarto, Kabupaten Sukoharjo - Dimas Aji Pratama; Dwiki Fitri; Aidatul Mufidah; Amalia Agamasi (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2026)
Stunting is a chronic nutritional problem that remains a major public health challenge in Indonesia, including in Ngombakan Village, Polokarto District, Sukoharjo Regency. Moringa leaves (Moringa oleifera Lam.) are known as a superfood plant with nutritional content far exceeding conventional food ingredients, including protein, vitamin A, calcium, potassium, iron, and vitamin C, making them highly potential as a functional food for stunting prevention. This community service activity aims to improve the knowledge of mothers at the Posyandu of Ngombakan Village about stunting and the benefits of moringa leaves, while also introducing the innovation of moringa leaf pudding as a nutritious supplementary food for toddlers. The activity was carried out from August 13 to September 6, 2024 through 6 meetings at the posyandu using lecture methods, leaflet distribution, and pudding-making demonstrations. The results showed a significant increase in mothers' knowledge about stunting and the nutritional content of moringa leaves, as well as positive enthusiasm from participants in accepting moringa leaf pudding as an affordable and nutritious supplementary food alternative for toddlers.